EFFECTS OF "MAGIC BOX" IN INNOVATING INTERACTIVE MEDIA IN TEACHING VOCABULARY - Dibdyaningsih, Haris (English Teaching Journal, 2015)
Innovative way in teaching L2 learners can be considered as a challenging job while it can be facilitated by using "Magic Box" as a tool box consists of many stationeries, types of papers and reuse things to innovate new interactive media. The main purpose of this study was conducted to identify the role of "Magic Box" in innovating interactive media in teaching vocabulary. The samples participants of the study were 10 students of English Department of STKIP Al Hikmah Surabaya. They were chosen because of they have to practice their teaching skills start from first semester, so they should develop their vocabulary. The lecture will guide and show to the students how to innovate interactive media using âMagic Boxâ. This study was designed as a qualitative study with pre-test and post-test instruments allow lectures to empirically evaluate the effectiveness of "Magic Box" in innovating interactive media in learning vocabulary by the students through formative assessment. After analyzing the pre-test and post-test it was found that using "Magic Box" has the important and determine role in teaching vocabularies to the students, as it was not possible as well as learning with just repetition and memorizing methods. Furthermore, "Magic Box" has its potential as a tool box for innovate interactive media, be able to motivate students especially the passive one in the whole teaching learning process, and also trigger the students to be more creative in innovating interactive media to improve their vocabulary.